Employees as performers in knowledge intensive firms: role of knowledge sharing. Issue 7 (5th October 2015) - Iqbal, Salman; Toulson, Paul; Tweed, David
Abstract : Purpose: – The purpose of this paper is to investigate the effect of specific human resource management (HRM) practices on knowledge sharing behaviour among employees of knowledge intensive firms (KIFs). Design/methodology/approach: – Based on previous literature, a model is proposed for the study and hypotheses are formulated. The cross-sectional data set comes from a sample of 390 employees of 19 KIFs. Confirmatory factor analyses were employed to evaluate the reliability and validity of the measurement model and the research model was tested using structural equation modelling. Findings: – The results suggest that collaborative HRM practices have a direct positive effect on employees' knowledge sharing behaviour. Surprisingly, the authors find that employees' knowledge sharing behaviour is independent of reward systems and employees' recognition. The authors suggest that organisational learning environments based on collaborative HRM practices can help employees' knowledge sharing behaviour and improve the capability of both individual and organisational capability. Research limitations/implications: – Knowledge-sharing behaviour is examined using specific HRM practices. Findings should be confirmed using a larger sample, as well as through longitudinal study. Practical implications: – This study will be beneficial for researchers, practitioners, scholars, organisational leaders and employees. It will also be helpful for those interested in organisational structure and relationships across organisations in knowledge context. Originality/value: – This study makes a valuable contribution, given that there is a lack of empirical studies of this nature focusing on the South-East Asian region. The findings are more interesting given that the current study is based on employees' perceptions.